2007
DOI: 10.1515/cclm.2007.256
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variation in creatinine and cystatin C

Abstract: Intra-individual variations for serum creatinine and cystatin C were similar in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
2
14
0
1
Order By: Relevance
“…Our results thus indicate a considerable biological variation of s-Cys, independent of GFR. Repeated s-Cys determinations in 10 healthy young subjects showed a lower intra-individual variation of 4.55 % [27]. This lower variation can be explained by the variation of CL nr , which has less relative influence on s-Cys when GFR is normal than at lower values.…”
Section: Discussionmentioning
confidence: 82%
“…Our results thus indicate a considerable biological variation of s-Cys, independent of GFR. Repeated s-Cys determinations in 10 healthy young subjects showed a lower intra-individual variation of 4.55 % [27]. This lower variation can be explained by the variation of CL nr , which has less relative influence on s-Cys when GFR is normal than at lower values.…”
Section: Discussionmentioning
confidence: 82%
“…Because implementing manual adjudication in large-scale observational studies of AKI is not feasible, we sought to identify a quantitative rule that could be applied to a cohort of hospitalized patients to accurately classify changes in kidney function during hospitalization. The superiority of the mean outpatient creatinine in matching the adjudicated value may reflect a clinical recognition by the adjudicators that averaging multiple serum creatinine values, if available, reduces the inappropriate effect of outliers or the known effect of physiologic variation (18)(19)(20). This latter observation suggests that for a large proportion of patients at risk for AKI, baseline kidney function may be more accurately described as a range than as a single value.…”
Section: Discussionmentioning
confidence: 99%
“…This initial study has recently been refuted by works which have shown that the intra-individual variability of CysC, measured by the PENIA method with Siemens reagents is equivalent to that of creatinine (47,48).…”
Section: Intra-individual Variabilitymentioning
confidence: 99%